Accuracy and cost-effectiveness of dynamic contrast-enhanced CT in the characterisation of solitary pulmonary nodules—the SPUtNIk study. Issue 1 (14th October 2016) - Qureshi, N R; Rintoul, R C; Miles, K A; George, S; Harris, S; Madden, J; Cozens, K; Little, L A; Eichhorst, K; Jones, J; Moate, P; McClement, C; et al.
Abstract : Introduction: Solitary pulmonary nodules (SPNs) are common on CT. The most cost-effective investigation algorithm is still to be determined. Dynamic contrast-enhanced CT (DCE-CT) is an established diagnostic test not widely available in the UK currently. Methods and analysis: The SPUtNIk study will assess the diagnostic accuracy, clinical utility and cost-effectiveness of DCE-CT, alongside the current CT and 18-flurodeoxyglucose-positron emission tomography) ( 18 FDG-PET)-CT nodule characterisation strategies in the National Health Service (NHS). Image acquisition and data analysis for 18 FDG-PET-CT and DCE-CT will follow a standardised protocol with central review of 10% to ensure quality assurance. Decision analytic modelling will assess the likely costs and health outcomes resulting from incorporation of DCE-CT into management strategies for patients with SPNs. Ethics and dissemination: Approval has been granted by the South West Research Ethics Committee. Ethics reference number 12/SW/0206. The results of the trial will be presented at national and international meetings and published in an Health Technology Assessment (HTA) Monograph and in peer-reviewed journals. Trial registration number: ISRCTN30784948 ; Pre-results.